Customary Law of Dou Donggo Bima from the Perspective of Islamic and Indonesian Positive Law - Muhammad Mutawali (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2022)
The community (dou) of Donggo uses their local wisdom and customary law to deal with legal matters within its society. Both are believed as truth and fulfilling the sense of justice within the community that upheld peace values. Therefore, it has been preserved for a long time until today. Practically, customary law enforcement is implemented by a customary law institution called Lembaga Adat dan Syari’at Donggo/Donggo’s Customs and Sharia Council (LASDO). This study is a normative legal study with statutory, comparative, and case approaches putting three legal decisions of LASDO as its material object. Data are collected through interviews and studies of the relevant documents consisting of primary ones; customary law, jurisprudence, and Islamic law references, and the secondary one; relevant research results, and the works of legal experts. The statutory and comparative. analysis employed in this study led to the finding that the contemporary Donggo community still employs the customary laws, such as baja and flogging law in solving the criminal cases namely rape, theft, and adultery. The sanctions imposed by LASDO in these three cases are different from the punishments contained in the KUHP. While compared to Islamic law, there are similarities in spirit and type of punishment yet different in the sentence form.